Diagnostic Delays and Quality of Life in Japanese Patients with Pulmonary Hypertension: A Nationwide Survey - Noriko Murakami; Daiki Asano; Natsuko Tokushige; Junichi Omura; Megumi Watanabe; Seitaro Nomura; Hiroaki Kitaoka; Yuichi Tamura (Pulmonary Therapy)
Abstract Introduction Pulmonary hypertension (PH) is a rare and severe disorder that significantly affects patients’ lives. However, a comprehensive picture of the diagnosis and treatment of this condition in Japan remains unclear. This study aimed to elucidate these aspects by conducting a nationwide survey targeting patients with PH and treating physicians. Methods A cross-sectional survey was conducted among 160 patients with PH (119 with pulmonary arterial hypertension [PAH] and 41 with chronic thromboembolic pulmonary hypertension [CTEPH]), of whom 121 were female (75.6%), and 211 physicians across Japan. The questionnaires assessed patients’ diagnostic journey, employment status, communication with physicians regarding treatment goals, health-related quality of life (HRQoL), and medication adherence. Results Patients visited a mean of 2.3 medical facilities before receiving a PH diagnosis (PAH patients: 2.2 visits; CTEPH patients: 2.3 visits), with a mean time from symptom onset to diagnosis of 18.0 months (PAH: 20.2 months; CTEPH: 12.2 months). Employment and school attendance rates declined from 68.8% before diagnosis to 44.4% immediately after diagnosis, and further to 36.9% at the time of the survey. Discrepancies in communication about treatment goals were observed between patients and physicians, particularly in patients with CTEPH (82.9% of patients reported such discussions vs. 41.2% of treating physicians). Median HRQoL scores, as assessed by the emPHasis-10 questionnaire, indicated impairment (PAH: 21.5; CTEPH: 18.0), which worsened with increasing disease severity. Conclusion This nationwide study provides a comprehensive overview of the challenges faced by patients with PH in Japan. The findings suggest the essential need for earlier diagnosis, support for employment and education among patients, and improved patient-physician communication to reduce the burden of PH and enhance patient outcomes. Graphical abstract avaliable for this article. Graphical abstract